Poly(ethylene glycol) Hydrogel Scaffolds Containing Cell-Adhesive and Protease-Sensitive Peptides Support Microvessel Formation by Endothelial Progenitor Cells - Peters, Erica B. (Cell Mol Bioeng, 2015)
The development of stable, functional microvessels remains an important obstacle to overcome for tissue engineered organs and treatment of ischemia. Endothelial progenitor cells (EPCs) are a promising cell source for vascular tissue engineering as they are readily obtainable and carry the potential to differentiate towards all endothelial phenotypes. The aim of this study was to investigate the ability of human umbilical cord blood-derived EPCs to form vessel-like structures within a tissue engineering scaffold material, a cell-adhesive and proteolytically degradable poly(ethylene glycol) (PEG) hydrogel. EPCs in co-culture with angiogenic mural cells were encapsulated in hydrogel scaffolds by mixing with polymeric precursors and using a mild photocrosslinking process to form hydrogels with homogeneously dispersed cells. EPCs formed 3D microvessels networks that were stable for at least 30 days in culture, without the need for supplemental angiogenic growth factors. These 3D EPC microvessels displayed aspects of physiological microvasculature with lumen formation, expression of endothelial cell proteins (connexin 32, VE-cadherin, eNOS), basement membrane formation with collagen IV and laminin, perivascular investment of PDGFR-β and α-SMA positive cells, and EPC quiescence (<1% proliferating cells) by 2 weeks of co-culture. Our findings demonstrate the development of a novel, reductionist system that is well-defined and reproducible for studying progenitor cell-driven microvessel formation.